Local radiotherapy for pleural dissemination of thymic tumors after initial treatment. (25th May 2021) - Okazaki, Dai; Shibamoto, Yuta; Yanagi, Takeshi; Ishikura, Satoshi; Kondo, Takuhito; Yamada, Yuki; Niwa, Masanari
Abstract: Pleural dissemination is a common pattern of failure after initial treatment of thymoma and thymic carcinoma, but there is no standardized treatment. As these tumors are relatively radiosensitive, we investigated the effectiveness of radiotherapy. Twenty patients underwent 33 series of local radiotherapy for 96 pleural dissemination lesions after initial treatment. Conventional radiotherapy (CRT), tomotherapy, and combination of the two were employed in 19, 13, and 1 series, respectively. The median follow-up period after the first irradiation for pleural dissemination was 46 months (range, 14–161). For all 20 patients, overall survival (OS) rates from initial radiotherapy for pleural dissemination were 100% at three years and 86% at five years. Progression-free survival (PFS) rates after 33 series of radiotherapy were 30% at three years and 16% at five years. Local control (LC) rates for 96 lesions were 98% at three years and 96% at five years. In-field recurrence was observed in only two among the 96 lesions. One patient (5%) developed grade 3 radiation pneumonitis and another (5%) developed grade 3 pericardial effusion. No other serious adverse events were observed. When disseminated nodules can be covered within localized fields, local radiotherapy may be a treatment option. Using tomotherapy, multiple lesions can be treated safely.